Optimal design of a Hydrogen Refuelling Station (HRFS) powered by Hybrid Power System - Gokcek, Murat; Kale, Cihangir (Pergamon-Elsevier Science Ltd, 2018)
The use of hydrogen as transportation fuel is considered to be a favourable alternative to fossil fuels. It is believed that the development of fuel cell vehicles will greatly facilitate reduction of greenhouse gas emissions from the transportation sector due to the fact that these vehicles are fuelled by hydrogen, which can be produced by a wide range of processes using renewable energy sources. In order to promote the use of fuel cell vehicles, it is imperative to build the necessary facilities to support this need in the near future, including hydrogen refuelling stations powered by renewable power generation systems. In this study, techno-economic analysis was performed for a hydrogen refuelling station powered by two types of hybrid renewable power generation systems (wind-photovoltaic-battery and wind-battery systems) which will be installed on the island of Gokceada, Turkey. The analysis was carried out to assess the feasibility of the hydrogen refuelling station to refuel 25 vehicles on a daily basis throughout the year, using HOMER software. Based on the results, the levelized cost of hydrogen for the hydrogen refuelling station powered by the hybrid wind-photovoltaic-battery and wind-battery systems is $ 8.92/kg and $ 11.08/kg, respectively. The levelized cost of hydrogen was also determined for different variable parameters (wind speed, wind turbine hub height, solar irradiance, and project lifetime). It is concluded that the hydrogen refuelling station powered by the proposed renewable power generation systems may be feasible for the chosen site.
Keywords: Hydrogen refuelling station; Levelized cost of hydrogen; Renewable energy; Techno-economic analysis